The role of metformin in the modern strategy of treatment and prevention of type 2 diabetes mellitus - Olga Mikhailovna Smirnova (Endocrinology Research Centre, 2010)
Metformin is a major antihyperglycemic agent used for the treatment of DM2. Analysis of the mechanism of its action is presented. Cardioprotectiveand anticancer activities of metformin are discussed. Results of multicentre studied of metformin are described.